Discovery of a potent tyrosine kinase AXL inhibitor bearing the 3-((2, 3, 4, 5-tetrahydro-1H-benzo[d]azepin-7-yl)amino)pyrazine core. Issue 6 (15th March 2019) - Wang, Yueliang; Xing, Li; Ji, Yinchun; Ye, Jiqing; Dai, Yang; Gu, Wangting; Ai, Jing; Song, Zilan
Graphical abstract: Highlights: AXL has been a promising therapeutic target for cancers. A side-chain ring closure medicinal chemistry approach was conducted. 15c bearing the 3-((2, 3, 4, 5-tetrahydro-1 H -benzo[ d ]azepin-7-yl)amino)pyrazine core was found to be most potent. 15c exhibited high anti-proliferative activity with IC50 values of 0.3 nM. 15c showed acceptable PK properties with the oral bioavailability of 24.8%. Abstract: Starting from the recently launched FLT3/AXL multi-targeted inhibitor Gilteritinib (5 ), we conducted a side-chain ring closure medicinal chemistry approach leading to the identification of compound15c as a highly potent AXL inhibitor in the biochemical and cellular anti-proliferative assays, with IC50 values of 1.2 and 0.3 nM, respectively. Compared with the reference compound5, our new discovered AXL inhibitor15c is more potent in both assays.